2017
DOI: 10.2214/ajr.17.18179
|View full text |Cite
|
Sign up to set email alerts
|

Safety-Net Academic Hospital Experience in Following Up Noncritical Yet Potentially Significant Radiologist Recommendations

Abstract: Radiologists' recommendations contained in written reports of noncritical findings may not be consistently followed or acknowledged in the medical records. Our study shows that a few report recommendations that were not consistently followed or acknowledged contained findings that referred to potentially harmful conditions. The results triggered an investment in systems improvement at the studied institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…More than 90% of patients now have access to their medical records through an online portal [1]. Portal use is on the rise, with 28% of patients selfreporting portal use in 2017 compared with 14% in 2014 [2]. In a recent survey, most academic medical centers reported between 25% and 50% portal use [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 90% of patients now have access to their medical records through an online portal [1]. Portal use is on the rise, with 28% of patients selfreporting portal use in 2017 compared with 14% in 2014 [2]. In a recent survey, most academic medical centers reported between 25% and 50% portal use [3].…”
Section: Introductionmentioning
confidence: 99%
“…Immediate radiology report access has the potential to benefit patients, because studies have shown that patients who understand their disease processes are more likely to adhere to treatment plans and have better outcomes [2,7,8]. However, radiology reports are technical and often jargonladen documents intended for other physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Info-RADS was developed by a study team that included 3 faculty radiologists, 2 radiology trainees, a linguist, a group of patient family advisers at our institution, and a patient family adviser at the ACR. The study team agreed on a set of principles guiding Info-RADS development: (1) language should be as close to the sixth grade reading level as possible, ( 2) the messaging workflow should be least burdensome to radiologists, (3) messages should minimize patient-initiated contact with providers when not appropriate, and (4) messages should trigger patient-initiated contact with providers when appropriate. Info-RADS was conceived for use with outpatients, excluding patients with cancer and those with critical results.…”
Section: What We Didmentioning
confidence: 99%
“…
Patient access to health information through web portals has many benefits, including minimizing communication gaps where results could be lost or overlooked [1]. There is evidence, however, that a majority of patients are not able to understand radiology reports [2].
…”
mentioning
confidence: 99%
“…In one recent study, over one-third of all recommendations were not followed-up [3]. Of those not followed-up, 40% of recommendations were not acknowledged by the referring clinician and hence not followed up; 44% of those patients were at risk of significant harm-e.g., suspected cancer.…”
Section: Introductionmentioning
confidence: 99%